ANALYSIS OF ECONOMIC GROWTH AND INFLATION RATE OF UNEMPLOYMENT IN LAMPUNG PROVINCE - Achmad Subing (UBL, 2016)
Influence Analysis of economic growth and inflation rate against Unemployment in Lampung Province. One of the barriers of economic development of a country or a region is unemployment while the main purpose of economic development in the country is to improve people's welfare. In addition, Economic Development has associated with economic growth and higher inflation.Unemployment is a problem that is not easily overcome by a country or region and the high level of unemployment may cause social and economic problems. Such conditions can lower the level of prosperity and purchasing power. The lower the unemployment rate of a country, the more affluent people's lives, and vice versa. To overcome the problem of unemployment attention is required not only in terms of the micro but also in terms of the macro. Macro policies that must be considered include the problems of inflation and economic growth. To determine the link between economic growth and the rate of inflation to the increase in unemployment in Lampung province, in this study the researcher raised problem on How is the effect of economic growth and inflation rate against unemployment in Lampung either partially or simultaneously using secondary data in the form of time series during 2000-2013. Data obtained from the Central Statistics Agency (BPS), Bank Indonesia Representative Lampung, Lampung Provincial Population Office. The research method is explanatory research with multiple linear regression analysis techniques with significant level of 5 percent. The results showed that economic growth and inflation rates go together with significant impact on unemployment in Lampung province, partially significant effect on economic growth and have a negative correlation to unemployment, which means that when the economic growth rate increase, it will bring down unemployment. While the inflation rate has no significant effect on unemployment and inflation rate was positively related to unemployment in Lampung province; this means that if the inflation rate increases, unemployment will also rise. Thus, to reduce unemployment in Lampung provincewe need to increase economic growth and reduce the rate of inflation in order to increase public welfare in Lampung province to be achieved.